Thermodynamic study of oxyfuel gas turbines: from O2 production to CO2 abatement . - Silva, Fernanda Cristina Nascimento (2021)
On conventional offshore petroleum platforms, the combined heat and power production (CHP) currently depends on simple cycle gas turbine systems (SCGT) that operate at a lower efficiency and increased environmental impact compared to modern onshore thermoelectric plants. Additionally, the reduced space and the limited weight budget in offshore platforms have discouraged operators from integrating more efficient but also bulkier cogeneration cycles (e.g. combined cycles). In spite of these circumstances, more stringent environmental regulations of offshore oil and gas activities have progressively pressured companies to lean towards the integration of advanced cogeneration systems together with either customary or unconventional carbon capture approaches to maintain both higher power generation efficiencies and reduced CO2 emissions. Accordingly, the performance of a conventional offshore petroleum production platform (without a carbon capture system) is assessed and compared to other configurations based on either an amines-based chemical absorption system or oxyfuel combustion concepts (e.g. S-Graz and Allam Cycles) for CO2 capture purposes. Since the original power and heat requirements of the processing platform must be satisfied, an energy integration analysis is performed to determine the waste heat recovery opportunities, whereas the exergy method helps quantifying the most critical components that lead to the largest irreversibility and identifying the thermodynamic potential for enhanced cogeneration plants. As a result, the oxyfuel gas turbines cogeneration based plants, the Allam and the S-Graz cycles, present competitive exergy performances such as power exergy efficiencies of 42.63% and 27.10% compared to 25.41% and 23.59% exhibited by SCGT and post-combustion systems, respectively. Furthermore, those advanced systems allow for significant cutting down of atmospheric CO2 emissions while maintaining similar unit exergy costs and higher rates of heat recovery as shown by the pinch and exergy analysis.